Perubahan Desain Dengan Uji Model Fisik Bendung Gerak Karangnongko Tahap I, Sungai Bengawan Solo Hilir Kabupaten Bojonegoro Dan Blora - Chandrasasi, Dian; Priyantoro, Dwi (Fakultas Teknik, Universitas Brawijaya, 2015)
The purpose of the investigation of the physical model of Karangnongko barrage Phase I is to study the hydraulics flow conditions in the river due to the influence of the barrage and to determine the capacity of the gate to control and regulate the flow rate during the dry and rainy seasons. While the objectives of this investigation hydraulics physical model is to provide suggestions for improvements of design and recommendations of design in terms of hydraulics aspects of Karangnongko barrage. Three important points that obtained from the results of testing and analysis are as follows: On each gate opening operation does not cause symptoms of vortex and directions distribution of equitable velocity both upstream and downstream of the gates; Does not occur overtopping on the upstream of barrage when the flowing of discharge Q PMF and PMF REGIONAL , because the highest water level in the barrage upstream on +41.00 and +37.30 in the river downstream when the gate is fully opened; To avoid the vortex flow in the stilling basin it is recommended that operate 9 units barrage gate with openings evenly. With details of water level in the upstream +38.00 at the beginning of the rainy season, +40.00 during the dry season, and +41.00 during the flood discharge.Key words: Karangnongko barrage dam, the physical model test, design change.